Hak Menguasai Tanah oleh Negara dalam Penggunaan Tanah untuk Investasi - Evi Djuniarti (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2023)
Along with the enactment of Law Number 11 of 2020 concerning Job Creation which regulates land acquisition for investment, there are several conflicts about that. These investment provisions prevent investors to invest their capital in Indonesia. One way to fulfill investors' wishes is to carry out legal transplantation and harmonization. The problems are related to land control by the state for investment and the existence of investment laws and Job Creation laws which has problems with current legal provisions, as well as how to utilize transplantation in harmonization of laws and regulations governing investment. This article aims to find a solution to accelerate regulation through transplantation and harmonization of law in the land sector. This research uses normative juridical methods. The results found were that the investment regulations in the land sector, and the regulations in the job creation law, still overlap so that it becomes an obstacle for investors. Therefore, the acceleration of regulations to fulfill investors' desires is carried out through transplantation and legal harmonization.